Can Endothelin-1 Levels in Patients with Esophageal Variceal Bleeding at Admission Predict Rebleeding Within 5 Days? - Shaltout, Shaker Wagih; Messery, A. El; Elshabrawi, Ahmed; Amin, Ahmed I.; Elshennawy, Mostafa H.; Mortada, Metwaly Ibrahim; ElSherbiny, Walid; Elalfy, Hatem; Elhammady, Dina (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Portal hypertension complicating liver cirrhosis is associated with vascular resistance, possibly due to overexpression of humoral vasoconstrictors, including endothelin. The study aimed to evaluate the efficacy of serum endothelin-1 levels as a noninvasive predictor of early esophageal rebleeding (within 5 days) following endoscopic treatment. Materials and Methods: Of the patients presented to the endoscopy unit at Mansoura University Hospital, 50 patients were chosen for this study on the basis of endoscopically proven acute esophageal variceal bleeding consequent to hepatitis C viral infection complicated by liver cirrhosis and portal hypertension. Routine laboratory parameters and serum endothelin-1 levels were assessed prior to endoscopic treatment. Patients were divided into 2 groups depending on the development of early postendoscopic rebleeding. Group A consisted of 16 patients who developed rebleeding, while group B included 34 patients who did not. Statistical analysis was performed to determine the predictors of rebleeding. Results: Multivariate logistic regression demonstrated that endothelin-1 level (P < .001) and serum albumin level (P = .04) were independent risk factors for early rebleeding. The most efficient cutoff value for endothelin-1 levels in predicting variceal rebleeding within the 5 days after endoscopic intervention was 65.29, which had an 88.2% specificity, 87.5% sensitivity, 88% accuracy, and area under the curve value of 0.89. In addition, hemoglobin, albumin, and creatinine levels were significantly different between bleeding and nonrebleeding groups (P = .03, P = .014, and P <.001, respectively), as was the duration of hospital stay (P < .001). Conclusion: Serum endothelin-1 levels appear to be a reliable, practical, noninvasive predictor of early variceal rebleeding and related comorbidities such as the severity of kidney affection and duration of hospital stay Cite this article as: Wagih Shaltout S, El Messery A, Elshabrawi A, et al. Can endothelin-1 levels in patients with esophageal variceal bleeding at admission predict rebleeding within 5 days? Turk J Gastroenterol. 2024;35(2):136-142.